Leaving Berlin : a novel - Kanon, Joseph (Atria Books, 2015)
Targeted by McCarthyism for his prewar politics, a young Jewish writer who fled the Nazis to America makes a desperate bargain with a fledgling CIA to work as a spy in a decimated Berlin.